HEALTH IS THE ONLY WEALTH - Sharopova Muazzam Sobirjonovna (Journal of new century innovations, 2022)
Abstract: The health of a person depends on him in many ways. For this, he should lead his life rationally, follow the requirements of a healthy lifestyle and lifestyle to prevent any disease." (From the speech of the President of the Republic of Uzbekistan I. Karimov on December 7, 2004)